Videovernehmung kindlicher Zeugen zur Praxis des Zeugenschutzgesetzes - Scheumer, Maike (Universitätsverlag Göttingen, 2007)
The author examines the practice of video interrogation for children witnesses. Starting point for their empirical investigation is the question of whether the law reform is not only meant well, but can be implemented practically. Here the author builds on the regulations of the 1998 established law for witness protection, to its feasibility in terms of the intended effective protection of victims, particularly the avoidance of so-called secondary victimization (trauma), experts from the federal state of Lower Saxony - prosecutors, police and courts - report by their own experiencees. In five selected district courts of Lower Saxony, the author has also conducted an extensive document analysis on the use of video testimony, and concluded that the video technology in criminal proceedings is used rarely. In specific reform proposals "de lege ferenda" also the recent regulations of the Law Reform Act of 2003 victims are included in the evaluative study.